Fighting the Constitution: A rebuttal to arguments for constitutional innovation - Cruz Apaza, Rodrigo René (2023)
After the tragicomic attempted coup d'état performed by former President José Pedro Castillo Terrones, the embers of a «new Constitution» were fanned to such an extent that no innovative proposals for a constitutional process were raised. The current Peruvian Constitution (1993) has been criticized from different political, legal and economic perspectives, but based on its regulating framework and the political society enforcing them, it has generated acceptable levels of stability in the aforementioned areas. Hence, this being the sociopolitical situation, it is necessary to delve into the subject matter in order to present to the academic community and, thereafter, to the Peruvian population, a review of the reasons in favor of a new Constitution to determine whether these are reasonable claims or mere allegations used to fight against the Constitution.